Magnetically separable ternary CdFe2O4/Fe2O3/CeO2 nanocomposites for visible-light photodegradation of eosin Y - Maryam Rezaei; Hanieh Ansarinejad; Ahmad Akbari; Forat H. Alsultany; Hadil Hussain Hamza; Masoud Salavati-Niasari (Results in Engineering)
The present work focuses on the development of ternary CdFe2O4/Fe2O3/CeO2 nanocomposites as photocatalyst via the facile and inexpensive auto-combustion method. In this approach, maleic acid was used as the capping and fuel agent and Tetraethylenepentamine, ethylenediamine, NaOH and NH3 were employed as alkaline agents. Physico-chemical properties of as-fabricated nanocomposites characterized by several methods including x-ray diffraction (XRD), field emission-scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), energy dispersive x-ray spectroscopy (EDS), Fourier transform-infrared spectroscopy (FT-IR), diffuse reflectance spectroscopy (DRS), vibrating sample magnetometer (VSM), and N2 gas absorption/desorption analysis or Brunauer-Emmett-Tellers (BET). Based on DRS analysis, the band gap of the three-component CdFe2O4/Fe2O3/CeO2 nanocomposite was obtained to be 2.0 eV, indicating that CdFe2O4/Fe2O3/CeO2 nanostructure can act as a photocatalyst under visible light. The photocatalytic activity of CdFe2O4/Fe2O3/CeO2 nanostructures was investigated against eosin Y (EY) and Malachite green (MG) pollutants. Also, the photocatalytic reaction mechanism was studied using EDTA, benzoic acid and ascorbic acid as scavengers. The results presented that under optimal conditions, EY and MG dyes were degraded to be 84.59 % and 76.77 %, respectively. Given the impressive photocatalytic performance demonstrated in this study, the CdFe2O4/Fe2O3/CeO2 nanocomposite shows strong potential as an effective catalyst for removing both anionic and cationic organic pollutants from aqueous solutions.